Combination of early constraint-induced movement therapy and fasudil enhances motor recovery after ischemic stroke in rats. (1st February 2016) - Liu, Yun-hai; Zhao, Yan; Huang, Feng-zhen; Chen, Yun-hong; Wang, Hong-xing; Bonney, Emmanuel; Liu, Bao-qiong
Abstract : Purpose: Constraint-induced movement therapy (CIMT) is a promising technique for the recovery of upper extremity movement in chronic stroke patients. However, the effectiveness of its use in acute ischemia has not been confirmed. Myelin-associated inhibitors, which have upregulated functions in tissues affected by acute focal infarction, limit axonal regeneration via activation of the Rho–Rho-associated protein kinase (ROCK) pathway. The present study examined whether early CIMT combined with the ROCK inhibitor fasudil promotes motor recovery after acute ischemic stroke. Materials and Methods: Rats were trained to perform the skilled-reach test and then subjected to middle cerebral artery occlusion (MCAO), producing a stroke affecting the preferred forelimb. Rats were assigned to one of four groups ( N = 6/group): (nontreated) Control, CIMT, Fasudil, or CIMT+fasudil. CIMT and/or intraperitoneal infusion of fasudil were initiated 1 day postMCAO. Skilled reach and foot fault test data were collected once before and repeatedly over 4 weeks after the operation. Infarct volumes were calculated. Results: All four groups showed similar forelimb impairment before treatment. The performance of CIMT alone group was similar to that of controls on both tests. Fasudil alone facilitated recovery in the foot-fault test, but not in the skilled-reach test. Rats in the CIMT+fasudil group demonstrated enhanced recovery in both tests, including better performance over time than the Fasudil group on the foot-fault test. Infarct size did not differ significantly between the groups. Conclusions: Early CIMT promotes motor recovery after acute ischemic stroke when it is administered with fasudil pharmacotherapy, but not without it.